Research Note: Effect of Simulated Shipping Temperatures on the Sensory Composition of South African Chenin Blanc and Sauvignon Blanc Wines - du Toit, W.J.; Piquet, C. (South African Journal of Enology and Viticulture, 2016)
This work investigated the effect of constant and simulated shipping temperatures on the sensory composition of Chenin blanc and Sauvignon blanc wines. Wines exposed to elevated temperatures during the trial developed unwanted aromas, such as over-aged, sulphur-like and a yellow colour, while those left at a cooler temperature retained tropical aromas. However, varying temperatures did not lead to large aroma differences in wines compared to those left at a constant lower temperature. It thus seems that average temperatures play a larger role in the development of unwanted over-aged aromas in certain South African white wines than temperature variations.